2000
DOI: 10.1068/a3332
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Models of Retail Rents

Abstract: The authors model retail rents in the United Kingdom with use of vector-autoregressive and time-series models. Two retail rent series are used, compiled by LaSalle Investment Management and CB Hillier Parker, and the emphasis is on forecasting. The results suggest that the use of the vector-autoregression and time-series models in this paper can pick up important features of the data that are useful for forecasting purposes. The relative forecasting performance of the models appears to be subject to the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…The approach has also been used in papers that have compared alternative forecasting approaches. Brooks and Tsolacos (2000) compare ARIMA models with a number of OLS and VAR based models in the context of British retail property, while Stevenson and McGrath (2003) compare a number of alternative approaches using London office market data.…”
Section: Introductionmentioning
confidence: 99%
“…The approach has also been used in papers that have compared alternative forecasting approaches. Brooks and Tsolacos (2000) compare ARIMA models with a number of OLS and VAR based models in the context of British retail property, while Stevenson and McGrath (2003) compare a number of alternative approaches using London office market data.…”
Section: Introductionmentioning
confidence: 99%
“…Property market models have the overriding aim of predicting reasonable estimates of key dependent variables: demand, supply, rent, returns, yield, vacancy, and cashflows based on information at hand (Brooks and Tsolacos, 2000, 2001Chaplin, 1998Chaplin, , 1999Chaplin, , 2000Matysiak and Tsolacos, 2003). The changes of these variables can be quantified by the internal and the external determinants within which the decisions are made in the market (Higgins, 2000).…”
Section: Commercial Property Market Forecastingmentioning
confidence: 99%
“…VARs have been used in a number of studies modelling house price dynamics Zhou, 1997;Guirguis et al, 2005) and have also been found to be extremely useful in a forecasting context in commercial real estate markets (e.g. Brooks & Tsolacos, 2000;Stevenson & McGrath, 2003). The VAR model used in this study is similar to that adopted by Stevenson & McGrath (2003) in their analysis of London office market and follows a Bayesian approach.…”
Section: Vector Autoregression Modelmentioning
confidence: 99%